LEFT VENTRICLE TORSION IN AN IDIOPATHIC HIS LEFT BUNDLE BRANCH BLOCK - E. N. Pavlyukova; D. A. Kuzhel (Российский кардиологический журнал, 2017)
The role of left His bundle branch block (LBBB) in normal systolic function of the left ventricle (LV) remains under investigated for the global deformation and torsion.Aim. To investigate on the global deformity of the LV in longitudinal direction by circumference, and its torsion, in patients with idiopathic LBBB with saved LV ejection fraction (EF).Material and methods. Totally, 50 persons with idiopathic LBBB studied, with the mean duration of QRS 153±24,5 ms. Comparison group included 18 persons with no LBBB. All patients underwent echocardiography (Echo) with assessment of intracardiac hemodynamics, deformity measurement by Speckle tracking imaging, with evaluation of torsion and rotation dynamics of the LV. Results. There were no significant differences in idiopathic LBBB group comparing to the controls, by the value of end-diastolic volume (respectively, 110,5±33,5 mL vs 95,3±23,5 mL, р=0,1) and EF LV (61,3±9,5% vs 64,4±9,4%, р=0,2). In idiopathic LBBB group comparing to controls, there was decrease of global LV deformation in longitudinal direction (respectively, -14,6±3,98% vs -8,4±3,10%, р=0,0006) and by circumference at basal segments (-7,02±4,40)% vs -10,6±4,18%, р=0,0075). It was found that in idiopathic LBBB there is disordered rotation at basal segments level (-2,95±4,36º vs -6,10±3,01º, р=0,019) and the torsion of LV as well (7,52±5,48º vs 13,1±5,18º, р=0,001).Conclusion. Disordered conduction in LBBB is followed by impaired rotation and torsion, regardless of the saved systolic function.